2008
DOI: 10.1016/j.ydbio.2008.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of testis-specific SOX9 activation requires high-glucose metabolism in mouse sex differentiation

Abstract: In mouse sex differentiation, SRY promotes Sertoli cell differentiation via SOX9 action, resulting in testis formation. SRY/SOX9 also initiates various testis-specific morphogenic events including glycogenesis in pre-Sertoli cells, suggesting the importance of glucose storage for certain SRY/SOX9-downstream events in gonadal sex determination. However, it remains unclear which cell types and what molecular/cellular events require sex-dimorphic high-energy metabolic rate. Here we show that the establishment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 48 publications
0
36
0
Order By: Relevance
“…These regulatory loops induce the activation of other downstream male pathway events, such as Amh expression, cell proliferation in the coelomic epithelium (see Glossary, Box 1), cell migration from the mesonephros (see Glossary, Box 1) and testis-specific glycogenesis (Martineau et al, 1997;Capel et al, 1999;Schmahl et al, 2000;Schepers et al, 2003;Matoba et al, 2005;Matoba et al, 2008).…”
Section: Primermentioning
confidence: 99%
“…These regulatory loops induce the activation of other downstream male pathway events, such as Amh expression, cell proliferation in the coelomic epithelium (see Glossary, Box 1), cell migration from the mesonephros (see Glossary, Box 1) and testis-specific glycogenesis (Martineau et al, 1997;Capel et al, 1999;Schmahl et al, 2000;Schepers et al, 2003;Matoba et al, 2005;Matoba et al, 2008).…”
Section: Primermentioning
confidence: 99%
“…Inc.; 7.5 mM) (Bowles et al, 2006). The segment culture assay using anterior, middle and posterior segments of the genital ridge (Hiramatsu et al, 2003) and the gonad culture without adjacent mesonephros Matoba et al, 2008) were also initiated from the XX Tg gonads at 14-15 ts. In addition, under the present culture conditions of XX and XY genital ridges initiated at 11.5 d.p.c., the gonadal explants at the 1st, 3rd and 5th day after culture roughly correspond to the testes/ovaries at 12.0-12.5, 13.5-14.5 and 15.5 d.p.c., respectively (Byskov, 1978;Taketo and Koide, 1981;Kanai et al, 1991;Mizukami et al, 2008;Hiramatsu et al, 2003;Hiramatsu et al, 2009;Hiramatsu et al, 2010;Wu et al, 2013).…”
Section: Organ Culturementioning
confidence: 99%
“…Besides this, feedforward pathways of Sox9 gene expression with the classic FGF9 signaling pathway (Kim et al, 2006) and, more recently, with a high-glucose metabolic state through an extracellular matrix (ECM) (Matoba et al, 2008), were shown to be necessary for the maintenance of Sox9 transcription and subsequently for Sertoli cell differentiation and testis cord formation. In this study, we have revealed that the PGD2 signaling pathway is likely to act independently of FGF9, thus implicating two independent feedforward loops between Sox9/Fgf9 (Kim et al, 2006) and Sox9/L-Pgds in the coordination of growth, cell differentiation and morphogenesis of the gonad.…”
Section: Research Articlementioning
confidence: 99%